2021
DOI: 10.1097/jxx.0000000000000626
|View full text |Cite
|
Sign up to set email alerts
|

Expansion of telehealth in primary care during the COVID-19 pandemic: benefits and barriers

Abstract: The novel coronavirus disease 2019 (COVID-19) pandemic remarkably accelerated the adoption of telemedicine in outpatient settings. Out of necessity, virtual care became a preferred and default modality of extending primary care services to health care consumers. Although telemedicine is not a new concept and had been used in many organizations and health systems, the COVID-19 pandemic scaled up its use in a variety of health care settings. Telehealth's use in primary care was particularly important because of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 24 publications
1
15
0
Order By: Relevance
“…Virtual care has been shown to improve access to care for patients, 25,35,36 and lower administrative costs and burdens for health care systems while maintaining patient and provider satisfaction. [5][6][7][8][9][37][38][39][40] Virtual care is becoming more acceptable in APC settings, especially for treating noncomplicated conditions such as UTIs. [21][22][23]41,42 A systematic review of virtual care in urology reported 5 retrospective studies that assessed using virtual care to manage UTIs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Virtual care has been shown to improve access to care for patients, 25,35,36 and lower administrative costs and burdens for health care systems while maintaining patient and provider satisfaction. [5][6][7][8][9][37][38][39][40] Virtual care is becoming more acceptable in APC settings, especially for treating noncomplicated conditions such as UTIs. [21][22][23]41,42 A systematic review of virtual care in urology reported 5 retrospective studies that assessed using virtual care to manage UTIs.…”
Section: Discussionmentioning
confidence: 99%
“…Virtual care has been shown to improve access to care for patients,25,35,36 and lower administrative costs and burdens for health care systems while maintaining patient and provider satisfaction 5–9,37–40. Virtual care is becoming more acceptable in APC settings, especially for treating noncomplicated conditions such as UTIs 21–23,41,42.…”
Section: Discussionmentioning
confidence: 99%
“…Asynchronous messages is another virtual communication system for patients and clinicians to discuss non-urgent related topics such as scheduling appointments, test results, and questions about medications [44] . More patients are utilizing online messaging systems due to its convenient nature, improving patient satisfaction [45] . Studies have acknowledged clinicians agree asynchronous messaging systems are effective and have increased their efficiency; however, it has also greatly increased their workloads.…”
Section: Discussionmentioning
confidence: 99%
“…Governmental restrictions and lockdowns of entire populations affected health systems and disrupted the routine treatment and follow‐up of non‐COVID‐19 patients (Ohannessian et al, 2020). To meet and adequately address the medical needs of most patients, while reducing patients’ and caregivers’ risk of infection, health systems had to start providing remote medical services (telemedicine) immediately (Chang et al, 2021; Dhaliwal et al, 2021; Wilhite et al, 2021).…”
Section: Introductionmentioning
confidence: 99%